Controlling Supplier Supply Stability with High Demand During the Covid-19 Pandemic at PT PQS - Santoso, Sugeng; Anjela, Lia; Alvionita, Uci; Firmansyah, Firmansyah; Etlanda, Khoirul Akbar; Fatmawati, Ari Ana (International Journal of Mechanical Engineering Technologies and Applications, 2022)
COVID-19 with a snap into a very influential factor in all sectors of the economy worldwide.Â The decrease in demand is also strongly felt in the manufacturing sector in Indonesia, even there are some factories were forced to have to lay off thousands of employees because it is not able to pay the salaries of employees.Â The opposite condition was experienced by PTÂ PQSÂ Indonesia, which experienced an increase in demand by 40% compared to the average demand for 6 months beforeÂ COVID-19,Â because some of the company's branches in other countries had stopped production because they had to follow local government policies. Eventually all orders were sent to be produced at PTÂ PQSÂ Indonesia. The increase in demand does not mean that PTÂ PQSÂ Indonesia did not experience obstacles during theÂ COVID-19Â pandemic, the problem faced was the decline in delivery performance from suppliers,Â which impacted on the reduced stock of raw material stock and could even lead to production stops.Â ThisÂ is because the suppliers were affected by Covid-19.Â This is a challenge because PTÂ PQSÂ has dozens of suppliers at home and abroad. To repeat this so that production does not stop, PTÂ PQSÂ Indonesia added a feature to help control supplier delivery performance. In 2018 the average delivery performance is only 60%Â â€”Â 70%, and the management target is 90% for local suppliers and 85% for overseas. ThisÂ â€œSupplier Delivery Performanceâ€Â feature really helps the procurement team to control the arrival of goods and provide information to suppliers related to their delivery performance,Â as well as being one of theÂ indexÂ KPIs to evaluate supplier performance for one year before the Annual Vendor Meeting is held. To create aÂ â€œSupplier Delivery Performanceâ€Â index, PTÂ PQSÂ must also create SOPs or standardize them so that all relevant suppliers and procurement teams can easily understand them.Â